TWO NEW HYBRID DAFFODILS (NARCISSUS, AMARYLLIDACEAE) FROM NORTHERN EXTREMADURA (CÁCERES, SPAIN) - Escobar García, Pedro (Phytotaxa, 2019)
Hybridization is since long time considered a major force shaping the diversity of daffodils. Following the description of Narcissus vitekii in 2018, the presence of its hybrids with other surrounding species at its remarkably diverse typus locality was expected, as the Sierra de Gata (Extremadura, Spain) sustains ample populations of 7 sympatric species of daffodils growing in immediate vicinity across the ecological gradient of the mountain. Many of these species hybridize, especially N. triandrus subsp. pallidulus. Here, we focus on two hitherto unreported hybrids found at the aforementioned site during the spring of 2018: Narcissus × richardianus (N. triandrus subsp. pallidulus × N. vitekii) and Narcissus × kirchnerianus (N. rupicola × N. vitekii).